Endemic flora within communities of mountain pine (pinus mugo turra) at metohian prokletije mountain - Cvetković Daniela Ž.; Amidžić Lidija B. (Zbornik Matice Srpske za Prirodne Nauke, 2023)
Metohian Prokletije is marked as one of the main European centers of the Balkan floristic endemism due to their geographical position on the fringe of the Mediterranean Sea and complex and diverse geomorphological, geological, orographic and climatic factors. This paper presents the results of long-standing comprehensive floristic researches of endemic flora in the Metohian Prokletije Mt., with particular reference to their high mountainous areas over the tree limit where Pinus mugo communities are concentrated. These types of ecosystems represent a transitional zone between the coniferous forests and high mountain bushy and herbaceous vegetation, at an altitude of 1,700 m do 2,400 m. Based on detailed field surveys, 118 Balkan endemic plant taxa within these communities were recorded so far. The phytogeographical analysis showed that the Balkan endemic taxa predominantly belong to the South-European mountainous (SEM) and Central-European mountainous (CEM) chorological groups with the following participation of floristic elements: 1) Dinaric-Scardo-Pindhian-Moesian (44 taxa or 37%), 2) Dinaric-Scardo-Pindhian (40 taxa or 34%), 3) Dinaric (24 taxa or 20%), and 4) Dinaric-Moesian elements (10 taxa or 9%). The biological spectrum was characterized by the prevalence of hemicryptophytes and chamaephytes. The obtained results on the presence of numerous endemic plants in the studied area can increase the interest in further floristic research, while the provided information of the ecological importance as well conservation status of threatened plant communities with Pinus mugo aimed at encouraging more effective biodiversity protection and sustainable management of natural resources.